Tawḥid. The language and structure of unknown Samaritan poems - Florentin, Moshe (In:Hebrew Union College-Jewish Institute of Religion;Hebrew Union College annual / Jewish Institute of Religion;Cincinnati, Ohio : College, 1953;77(2006), Seite 167-178, 2006)
In this paper I present several samples of a hitherto unknown type of Samaritan liturgical poem called Tawḥīd. Written in Samaritan Hebrew and Aramaic, the main motif of these poems is
Keywords: Poetik; Samaritaner